Anterior abdominal wall defects managed at a tertiary maternal‐fetal medicine service in New Zealand: What counselling advice can we offer parents?. (6th March 2019) - Narang, Apoorv; Carlsen, Victoria; Long, Audrey; Battin, Malcolm; Upadhyay, Vipul; Sadler, Lynn; Stone, Peter
Abstract : Background: Anterior abdominal wall defects, including gastroschisis and omphalocoele, are common fetal anomalies. The management remains complicated, and their diagnosis may lead to significant parental distress. Effective parental counselling may impact on parental perceptions of the defect and help guide pregnancy management. Aims: Using contemporary data, we aimed to describe clinical outcomes of patients with gastroschisis or omphalocoele in order to provide information for clinicians to assist in parental counselling. Materials and Methods: We followed a case‐series of patients with anterior abdominal wall defects referred to our regional Maternal Fetal Medicine services from 2011 to 2016. Outcomes of interest antenatally included details of diagnosis, associated anomalies and outcomes of pregnancy and postnatally included the nature of surgical repair, hospital stay and secondary complications until initial discharge. Results: Eighty babies with gastroschisis were referred antenatally, and 72 were liveborn. Forty‐nine babies with omphalocoele were referred antenatally, and 24 were liveborn. One further neonate with omphalocoele was postnatally diagnosed. Seventy‐one neonates with gastroschisis progressed to operation, 30 developed complications post‐surgery, and 68 survived until initial discharge. Twenty‐two neonates with omphalocoele progressed to surgery, only two developed complications, and 21 survived until initial discharge. Eight of the surviving neonates with omphalocoele had associated structural abnormalities. The median hospital stay was 27 and eight days for gastroschisis and omphalocoele, respectively. Conclusion: Neonates with gastroschisis can have complex postnatal periods. Omphalocoele is associated with high antenatal mortality, especially in the presence of associated abnormalities; however, surviving neonates may have uneventful postnatal periods.